HUBUNGAN ANTARA KONSENTRASI BELAJAR DENGAN TINGKAT PENGGUNAAN MEDIA SOSIAL TIKTOK PADA MAHASISWA FAKULTAS USHULUDDIN ADAB DAN DAKWAH IAIN PAREPARE - Herman, Tasya Safitri; Saleh, Muhammad (Institut Agama Islam Negeri Parepare, 2025)
This research explains the relationship between study concentration and the level of use of TikTok social media among students at the Ushuluddin Adab and Da'wah Faculty at IAIN Parepare. The aim of this research is to determine the relationship between study concentration and the level of use of TikTok social media among students at the Ushuluddin Adab and Da'wah Faculty of IAIN Parepare. The research method used is an associative quantitative method with data collection techniques using a questionnaire instrument which was announced to 40 students of the Ushuluddin Adab and Da'wah Faculty of IAIN Parepare with data analysis using the classic Assumption Test and research hypothesis testing. The results of the research, namely the relationship between study concentration and the level of use of TikTok social media among students at the Ushuluddin Adab and Da'wah Faculty of IAIN Parepare, show that Ho is accepted with the statement that there is a relationship between study concentration and the level of use of TikTok social media among students at the Ushuluddin Adab and Da'wah Faculty of IAIN Parepare. from the sig (2-tailed) value, namely 0.000 < 0.05 and the relationship level value, namely 0.620 in the Strong Relationship category with data interpretation that there is a tendency that the use of TikTok social media contributes positively to student learning concentration.